George's marvellous medicine - Dahl, Roald (Puffin, 2016)
George Kranky's Grandma is a miserable grouch. George really hates that horrid old witchy woman. One Saturday morning, George is in charge of giving Grandma her medicine. So-ho! Ah-ha! Ho-hum! George knows exactly what to do. A magic medicine* it will be. One that will either cure her completely ...or blow off the top of her head. *WARNING: Do not try to make George's Marvellous Medicine yourselves at home. It could be dangerous. Ages 9+